2014
DOI: 10.1002/msb.134947
|View full text |Cite
|
Sign up to set email alerts
|

Digital cell quantification identifies global immune cell dynamics during influenza infection

Abstract: Hundreds of immune cell types work in coordination to maintain tissue homeostasis. Upon infection, dramatic changes occur with the localization, migration, and proliferation of the immune cells to first alert the body of the danger, confine it to limit spreading, and finally extinguish the threat and bring the tissue back to homeostasis. Since current technologies can follow the dynamics of only a limited number of cell types, we have yet to grasp the full complexity of global in vivo cell dynamics in normal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 48 publications
2
133
0
Order By: Relevance
“…This initial exon-intron analysis also suggested that some of the transcript changes observed in the triple KO spleens could be due to changes in the cellular composition of the triple KO tissues. In order to test this, we took two different approaches: first, we immunostained the spleen sections for the presence of various cell types, and second, we utilized the digital cell quantitation (DCQ) method (31) to investigate the relative quantities of various immune cell subpopulations in the triple KO spleens. Consistent with the impression of increased EMH observed in the H&E-stained sections of the triple KO mouse spleens, there were increases in staining for neutrophils and overall myeloid cells in the triple KO spleens, suggesting either extramedullary myelopoiesis or neutrophil infiltration of the tissue or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial exon-intron analysis also suggested that some of the transcript changes observed in the triple KO spleens could be due to changes in the cellular composition of the triple KO tissues. In order to test this, we took two different approaches: first, we immunostained the spleen sections for the presence of various cell types, and second, we utilized the digital cell quantitation (DCQ) method (31) to investigate the relative quantities of various immune cell subpopulations in the triple KO spleens. Consistent with the impression of increased EMH observed in the H&E-stained sections of the triple KO mouse spleens, there were increases in staining for neutrophils and overall myeloid cells in the triple KO spleens, suggesting either extramedullary myelopoiesis or neutrophil infiltration of the tissue or both.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemically stained slides were graded as described in Materials and Methods. Although not readily apparent in the examples shown in (31). This method uses the genome-wide transcriptional profiles of a tissue to identify changes in the quantities of at least 213 immune cell subpopulations.…”
Section: ------------Atttatttgttcctttgtacctgat-------------mentioning
confidence: 99%
“…More recently Newman et al [15] propose robust linear regression (RLR) and ν-SVR regression instead of L 2 based regression, which is highly susceptible to noise. Digital cell quantification (DCQ) [23] is another approach designed for monitoring the immune system during infection. Compared to prior methods, DCQ forces sparsity by combining R 2 and R 1 regularization into an elastic net.…”
Section: Overview Of Prior In Silico Deconvolution Methodsmentioning
confidence: 99%
“…The data were transformed by dividing each gene expression entry by the standard deviation across test samples. Analysis of relative cell quantity was run with three repeats and a lambda minimum of 0.2 as previously described (39).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The DCQ is a previously validated algorithm that leverages cell type-specific whole-genome transcriptional expression profiles derived from 207 immune cells (Immgen; reviewed in reference 46) to infer changes in immune cell quantities based on cell-specific surface markers (39). We used the DCQ to derive the relative quantity of predicted cells within the infected lung and infer their activation states.…”
Section: Pb2 Is a Key Driver Of Inflammatory Responses Enhancing Immumentioning
confidence: 99%